(untitled) - Parra, Viviana Gladys; Díaz, F.; Aguirre, M. (Universidad Nacional de Cuyo. Facultad de Ciencias Médicas)

Acantosis Nigricans (2014)

(untitled)
Fil: Parra, Viviana Gladys. Hospital Luis Lagomaggiore (Mendoza, Argentina). Servicio de Dermatología